Structural analysis of IPC zeolites and related materials using positron annihilation spectroscopy and high-resolution argon adsorption. Issue 22 (23rd May 2016) - Jagiello, J.; Sterling, M.; Eliášová, P.; Opanasenko, M.; Zukal, A.; Morris, R. E.; Navaro, M.; Mayoral, A.; Crivelli, P.; Warringham, R.; Mitchell, S.; Pérez-Ramírez, J.; et al.
Abstract : Precise pore size analysis of isoreticular series of UTL related zeolites is performed using high-resolution argon adsorption and positron annihilation spectroscopy. Abstract : The advanced investigation of pore networks in isoreticular zeolites and mesoporous materials related to the IPC family was performed using high-resolution argon adsorption experiments coupled with the development of a state-of-the-art non-local density functional theory approach. The optimization of a kernel for model sorption isotherms for materials possessing the same layer structure, differing only in the interlayer connectivity ( e.g. oxygen bridges, single- or double-four-ring building units, mesoscale pillars etc. ) revealed remarkable differences in their porous systems. Using high-resolution adsorption data, the bimodal pore size distribution consistent with crystallographic data for IPC-6, IPC-7 and UTL samples is shown for the first time. A dynamic assessment by positron annihilation lifetime spectroscopy (PALS) provided complementary insights, simply distinguishing the enhanced accessibility of the pore network in samples incorporating mesoscale pillars and revealing the presence of a certain fraction of micropores undetected by gas sorption. Nonetheless, subtle differences in the pore size could not be discriminated based on the widely-applied Tao – Eldrup model. The combination of both methods can be useful for the advanced characterization of microporous, mesoporous and hierarchical materials.